Agglomeration of fines and sand in the separator - Fauzi, N.A.A.M. (Offshore Technology Conference, 2020)
Fines and sand capturing inside the separator is one of the methods to prevent solids carry over. Currently, there are ongoing studies to identify the suitable method to agglomerate the produced solids. Generally, heavier solids would be denser and easily settled at the bottom of the vessel, hence no solids carry over issues. Produced solids can be consisting of natural solids and/or artificial solids. Several types of polymers have been evaluated based on its agglomeration performance, rheology and compatibility as an approach to establish suitable particle size to minimize sand free rate. The procedures involved include bottle test experiments coupled with particle size distribution (PSD) analysis via Laser Particle Size Analyzer (LPSA). The materials used in the experiments are glass beads with sizes of 50µm and 100µm, synthetic water (0.1M NaCl), a cationic polymer and an anionic polymer. Both polymers have high molecular weight which is known to provide good agglomeration capacity. For each experiment, a 5g of glass bead was placed together with 90mL of synthetic water in a 100mL measuring cylinder. The system was then tested using three polymer system; i) a single cationic polymer system, ii) a single anionic polymer system and iii) a combination of both cationic and anionic polymer system. Light agitation was applied on each, PSD was evaluated and results compared to those of the untreated samples. The improvement of particle size distribution was observed for all three systems. The results will be discussed further in the paper. The novelty of this research is the application of the sand agglomeration mechanism towards surface sand capturing via separator. Copyright © 2020, Offshore Technology Conference.